What does surgical conscience mean to perioperative nurses: An interpretive description. Issue 2 (April 2022) - Duff, Jed; Bowen, Lynette; Gumuskaya, Oya
ABSTRACT: Background: Surgical Conscience is a unique concept that is central to the clinical practice of perioperative nurses. It is an abstract phenomenon that explains a nurse's moral obligation to safeguard surgical asepsis and patient safety. Despite being deeply rooted in perioperative tradition, the phenomenon is poorly understood and inadequately described. Aim: To generate insight into the phenomenon of Surgical Conscience by interpreting the experiences and perceptions of perioperative nurses. Methods: Semistructured in-depth interviews were conducted with 15 Australian perioperative nurses. Interview transcripts were reviewed to identify themes and patterns within the experiences and perceptions of the participants. These were then synthesised into a conceptual model of Surgical Conscience. Findings: Surgical Conscience was defined as 'the moral obligation to uphold and defend surgical asepsis and perioperative safety no matter the cost or consequence'. The conceptual model illustrates that a Surgical Conscience is dependent on the presence of three constructs: consciousness (knowing), conscience (feeling), and agency (acting) and is moderated by contextual factors such as education, training, mentorship, environment, culture, and support. Discussion: New insight into this phenomenon makes it evident that nurturing a Surgical Conscience requires a multifaceted approach that targets each of the constructs (knowing, feeling, acting) and the contextual factors. Conclusion: To optimise surgical asepsis and patient safety, perioperative leaders should evaluate their staff and department against the conceptual model and develop an evidence-informed program to address identified deficits.